NEUTRON REFLECTIVITY FROM A SILICON-NITRIDE LAYER ON A SILICON SUBSTRATE - Ashworth, C; Messoloras, S; Stewart, R; Wilkes, J; Baldwin, I; Penfold, J (1989)
The neutron reflectivity from a sample consisting of a silicon nitride layer on a crystalline silicon substrate has been measured. The structure of the sample normal to the reflecting surface has been modelled to produce a scattering length density profile whose simulated reflectivity matches that experimentally determined. The layer thickness and the corresponding interface structures are detailed. Two modelling techniques have been used, one based on the Born and Wolf matrices and the other based on the Abeles method. The two techniques are compared and the sensitivity of the two techniques are discussed.